'Unmute This': Captioning an (audio)visual microgenre. Issue 1 (1st December 2016) - Harper, Paula
I argue that 'Unmute This' videos constitute an Internet video microgenre, and as particular intersections of behaviour, devices and content, these videos function as an entry point into a number of broader issues within twenty-first–century audio-visual media and participatory behaviour. First, the moment of encounter with an 'Unmute This' video post elucidates a reframing of the digital sensorium: how ears and eyes, watching and listening, are configured and reconfigured in tandem with ubiquitous devices like smartphones and earbuds, and via the affordances and behaviours of various digital and social media platforms. Secondly, directives to 'Unmute This' point to a distinct mode of online socialization, a particular 'sociality' of social media. In collaboration with the devices and platforms of their everyday experience, users build a vernacular theory of media use based on their own behaviours and practices. They then implement that theory while seeking to impart an ideal content experience for others, platform users potentially far removed from the poster/commenter's own acquaintances. In this article, then, I begin by unpacking the implementation of autoplaying video and the assemblage of the ubiquitous digital sensorium – that is, what sensory behaviours and practices map on to dealing with autoplaying video, at least as suggested by 'Unmute This' directives. I then consider 'Unmute This' videos as a genre, sketching out some patterns in the form and content of videos that one might be most likely directed to 'UNMUTE IMMEDIATELY', and interrogating how such stylistic and formal details might be emergent in response to platform affordances, ubiquitous devices and norms of Internet-mediated sociality. Finally, I suggest a theorization of vernacular media theory, drawn from the particulars of 'Unmute This' videos and their creators and disseminators, and I unpack some implications for the kinds of assumptions about sociality, behaviour and trust that are built into such theorizing and user responses to it.